Level and predictors of mental health literacy among secondary school students in Nakhon Pathom Province, Thailand: 10.55131/jphd/2024/220305 - Rungsang, Benjamaporn; Juntorn, Sutinun (Journal of Public Health and Development, 2024)
Mental health literacy (MHL) is one of the most important factors in resolving mental health disorders for adolescents. This cross-sectional study examines the level of MHL among secondary school students and seeks to determine its predictors. A multi-stage sampling technique was used to recruit a sample of 404 students with a mean age of 14.89 years (SD = 1.66) attending an autonomous secondary school in Nakhon Pathom province, Thailand in the first semester of the 2023 academic year. The research instruments were two self-reporting questionnaires, namely the General Health Questionnaire (GHQ – Thai version) and the Mental Health Literacy Survey. Content validity was reviewed by three experts and the Index of Consistency (IOC) was 0.97, with Cronbach’s alpha reliabilities of 0.94 (GHQ), and 0.75 (MHL). Descriptive statistics including chi-square test and binary logistic regression were used to analyze the data. The mean score of MHL was 28.96 (SD = 3.58), indicating adequate MHL within this sample. Academic performance (OR 1.834, 95%Cl 1.139-2.954), studying at the senior high school level (OR 1.559, 95%Cl 1.005-2.418), and experiencing psychological distress (OR .535, 95%Cl .321- .892) were all predictors of adequate MHL. These findings suggest that school administrations and healthcare providers should develop a program to ensure junior-level students attain cognitive abilities and an adequate MHL level to prevent future mental illness.